Ambient dissolution–recrystallization towards large-scale preparation of V2O5 nanobelts for high-energy battery applications. (April 2016) - Rui, Xianhong; Tang, Yuxin; Malyi, Oleksandr I.; Gusak, Andriy; Zhang, Yanyan; Niu, Zhiqiang; Tan, Hui Teng; Persson, Clas; Chen, Xiaodong; Chen, Zhong; Yan, Qingyu
Abstract: Large-scale preparation of single-crystalline V2 O5 nanobelts is successfully demonstrated with a simple solution treatment process under ambient condition using commercial V2 O5 powders as the precursor. Unlike the commonly recognized Ostwald ripening process that involves the dissolution of small crystals and the redeposition of the dissolved species on the more energetically favored large particles, this preparation shows that the reaction mechanism of our method follows a different route, in which the large commercial V2 O5 powders (1–4 μm) dissolve in the solution and eventually transform into V2 O5 nanobelts with lengths up to several tens of micrometers, widths of 5–50 nm, and thicknesses of only ~5 nm. The density function theory (DFT) calculation indicates that the preferential growth of V2 O5 nanobelts along the [010] direction is attributed to the anisotropic bonding of V2 O5 layered structure resulting in the fastest nucleation rate at the V2 O5 (010) surface. These nanobelts possess a remarkably large surface area, which is about 14 times higher than that of the V2 O5 precursor. Binder-free bulky papers can be prepared by the intertwining V2 O5 nanobelts with the acid-treated multi-walled carbon nanotubes. When the V2 O5 nanobelts are applied as the cathodes in lithium-ion batteries (LIBs) and sodium-ion batteries (SIBs), such robust and flexible electrodes demonstrate superior lithium and sodium storage performances at fast charge/discharge rates, delivering 144 mA h g −1 at 20 C in LIBs and 61 mA h g −1 at 10 C in SIBs respectively. Graphical abstract: Highlights: Ambient and large-scale (in kilogram) preparation of V2 O5 nanobelts is performed. An intriguing dissolution–recrystallization process is observed. [010]-oriented growth of V2 O5 nanobelts is elucidated by density functional theory. These V2 O5 nanobelts can be fabricated into binder-free bulky paper electrodes. Superior Li and Na storage properties at fast charge/discharge rates are exhibited.